2020
DOI: 10.51791/njap.v47i5.1275
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effect of garlic (Allium sativum) and ginger (Zingiber officinale) and their combination on growth, rumen ecology and apparent nutrient digestibility in sheep

Abstract: Manipulation of rumen environment using herbal mixtures with antioxidant and antibacterial potentials will improve rumen health and animal productivity. This study undertook to assess the effect of supplementing garlic and ginger powder and their combination on rumen ecology and nutrient utilization of sheep. Sixteen mixed breed rams were allotted to four experimental diets in a completely randomized design. The experiment lasted for 91 days. The four diets were Control (No garlic or ginger powder), gap (garli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 2 publications
0
6
1
Order By: Relevance
“…However, ADG differed significantly among different weeks (2 nd , 7 th , 11 th weeks) as presented in Fig 1 A. Similarly, garlic powder supplementation up to 1.5% in diet did not affect the final weight and ADG of W est African Dwarf goats (Ikyume et al, 2017). In contrast with the present results, the addition of 2 g of dried garlic improved body weight gain in growing male buffaloes (Hassan and Abdel-Raheem, 2013).…”
Section: Animal Performancecontrasting
confidence: 66%
See 1 more Smart Citation
“…However, ADG differed significantly among different weeks (2 nd , 7 th , 11 th weeks) as presented in Fig 1 A. Similarly, garlic powder supplementation up to 1.5% in diet did not affect the final weight and ADG of W est African Dwarf goats (Ikyume et al, 2017). In contrast with the present results, the addition of 2 g of dried garlic improved body weight gain in growing male buffaloes (Hassan and Abdel-Raheem, 2013).…”
Section: Animal Performancecontrasting
confidence: 66%
“…In line with the present results, the apparent digestibility of DM, OM, aNDF and ADF were not affected by dietary supplementation with 40 g/d garlic powder, while CP digestibility tended to be decreased in beef cows (Wanapat et al, 2013). Additionally, 0.5-1.5% of garlic powder supplementation did not affect the digestion coefficients of DM, CF, EE, Ash, NDF and ADF and decreased CP digestibility in West African Dwarf goats (Ikyume et al, 2017).…”
Section: Effect Of Dietary Treatments On Nutrient Digestibilitymentioning
confidence: 76%
“…Nonetheless, dietary supplementation with garlic powder improves the growth performance (ADG and FCR) of lambs and calves primarily by increasing feed intake and nutrient digestibility. In contrast to the effects in lambs and calves mentioned above, for goats aged 6 to 7 mo, the provision of 5 to 15 g/kg (DM basis) of garlic powder for 84 d has no effect on growth performance and feed intake and can even decrease the digestibility of CP in a dose-dependent manner ( Ikyume et al., 2017 ). The reasons for this phenomenon are not clear and remain to be further investigated.…”
Section: Effects Of Garlic Products On the Growth Performance Of Rumi...mentioning
confidence: 99%
“…(2017) 10 27 d sheep 22 mo = = = Patra et al. (2011) 5, 10 and 15 84 d goats 6–7 mo = = = = = = = = = = = Ikyume et al. (2017) 7.5 150 d calves 2–3 mo = = Balamurugan et al.…”
Section: Effects Of Garlic Products On the Growth Performance Of Rumi...mentioning
confidence: 99%
“…In addition, it has been reported that ginger supplemented with the diets of pregnant sheep can increase milk yield and components, red and white blood cells (Hendawy et al, 2019). Also, it has been reported by Ikyume et al (2020) that ginger supplemented to sheep diets signi cantly increases daily body weight gain without affecting body weight, hay and concentrate feed consumption, and feed conversion ratio. However, they reported that while the total volatile fatty acids, propionate, acetate and butyrate values increased signi cantly, affected the rumen pH insigni cantly and also did not affect the rumen bacteria, fungi and protozoa populations.…”
Section: Introductionmentioning
confidence: 96%